Data Communication Security Design on IoT Based Systems with the Port Knocking Method - Putra, I Made Andre Dwi; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Technology is the thing that is familiar among the public and the Internet is something that is always used in everyday to help the work . With the technology and the internet, IOT (Internet of Things) can be realized in any device that is there to build the Smart City. However, there are still people who use the internet to commit crimes. To prevent it is not enough with a firewall alone but need the system of security that is over. In the article it discusses how port knocking would be able to help secure a system that is based IOT it.